Phylogeny of human populations in Papua New Guinea, a genetic and linguistic diversity hotspot - Kopicová, Klára (Jihočeská univerzita, 2020)
A detailed phylogeny of human populations in Papua New Guinea was constructed using exhaustive topology exploration, and the fit of the model to the data was improved by adding several admixture events. The analysis relied on published genome-wide SNP genotyping data for hundreds of individuals, and qpGraph was a principal method employed in the study for testing the fit of admixture graphs to the data.
Phylogeny of human populations in Papua New Guinea, a genetic and linguistic diversity hotspot
Keywords: Admixture graph; blood groups; common ancestry; D-statistic; f-statistic; genomic analyse; haplotypes; Highlanders; historical linguistic; Lowlanders; Papua New Guinea; PCA; phylogeny; sequencing; SNP; variance.